Investigating English teachers' understanding of English language assessment - Usman, Muhammad Syahid; Magdahalena Tjalla; Abdul Haris Sunubi (Universitas Terbuka, 2024)
A teacher is responsible for assessing students' work and should possess a clear understanding of assessment, testing, examination, and evaluation. However, in reality, there are instances where teachers encounter confusion when distinguishing between these terms, mistakenly perceiving them as synonymous. Moreover, the teachers' understanding of these terms also plays a critical role in facilitating meaningful learning experiences for students. Based on the reasons above, this research aimed to describe the English teachers’ understanding of English language assessment and how the teachers assess the students’ work. The research conducted on UPT SMA Negeri 1 Parepare. There were five English teachers as research subjects. The research method used was qualitative design. The data collected through interview. Analysis data with data collection, data reduction, data display, and the last is data conclusion and verification. The result of the research showed that the teachers’ understanding has difference and similarity as from five teachers. The difference was from four teachers, only one teacher that related to Assessment understanding and the similarity was four other teachers beside Assessment understanding which is the most dominant, their teachers’ understanding was also related to Instructional understanding, Subject matter understanding and Pedagogical understanding. The teachers’ assessment of the students prioritize learning by using a range of assessment methods such as daily tests, semester exams, and attitude assessments. Group activities and projects are also utilized to enhance confidence and encourage active learning.